2020
DOI: 10.3389/fendo.2020.00540
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Remodelling by Prenatal Betamethasone: Effects on β-Cells and Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is a multifactorial disease of unknown aetiology. Studies focusing on environment-related prenatal changes, which might have an influence on the development of T1D, are still missing. Drugs, such as betamethasone, are used during this critical period without exploring possible effects later in life. Betamethasone can interact with the development and function of the two main players in T1D, the immune system and the pancreatic β-cells. Short-term or persistent changes in any of these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…In fact, antenatal glucocorticoids have an important impact on immune system ontogeny [ 22 ] and modify the T cell receptor repertoire, as we demonstrated in NOD mice [ 17 ]. Our recent results also showed betamethasone effects on β -cell growth, metabolism, and immunogenicity [ 19 ]. Additional effects of glucocorticoids are epigenetic modifications [ 33 ] which could affect both the developing immune system and the β -cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, antenatal glucocorticoids have an important impact on immune system ontogeny [ 22 ] and modify the T cell receptor repertoire, as we demonstrated in NOD mice [ 17 ]. Our recent results also showed betamethasone effects on β -cell growth, metabolism, and immunogenicity [ 19 ]. Additional effects of glucocorticoids are epigenetic modifications [ 33 ] which could affect both the developing immune system and the β -cells.…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, synthetic glucocorticoids, most often betamethasone, are routinely administered to women at risk of preterm delivery between 24 and 34 weeks of gestation to accelerate lung maturation and reduce the severity of respiratory distress syndrome, therefore improving the survival rates of premature infants. Recent studies in experimental models of T1D show that prenatal betamethasone affects the two main players in this disease, the immune system and the pancreatic β -cells, and that corticosteroid-related changes may have long-term consequences in the offspring [ 17 19 ]. Since both the immune system and the pancreatic islets are still developing until birth, glucocorticoid exposure [ 20 ] may affect islet function [ 21 ] and T1D susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…ACS are also potent suppressors of inflammatory responses in the newborn during the first days after birth (Kemp et al, 2016). Following ACS treatment, immune cells in babies, especially neutrophils and macrophages, tend to demarginate from vascular wall and transiently reduce the production of cytokines (i.e., interlutin-6 (IL-6), IL-10 and tumor necrosis factor alpha (TNF-α)), chemokines and reactive oxygen species (ROS) (Fay et al, 2016;Holm et al, 2017;Perna-Barrull et al, 2020). Animal studies have demonstrated those molecules, especially IL-6 and TNF-α, are involved in sensitizing the developing retinal blood vessels to injuries such as oxygen changes, and cause subsequent neovascularization (Tremblay et al, 2013;Hong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth has previously been associated with increased risk of developing type 1 diabetes [26]. The higher risk of type 1 diabetes in preterm born children may be explained by reduced insulin sensitivity [40], gut dysbiosis [41], exposure to antenatal corticosteroids [42] and rapid weight gain in infancy [24] due to catch up growth [43]. Preterm children with CAs had a reduced risk of type 1 diabetes compared with children with CAs born at term, which was of borderline signi cance.…”
Section: Discussionmentioning
confidence: 99%